The Politics of Anglican Martyrdom: Letters to John Walker, 1704–1705 - Neufeld, Matthew (The journal of ecclesiastical history, 2011)
This article explores the political significance of past Christian suffering at the dawn of the Augustan era through an analysis of correspondence containing accounts of hardships endured by conforming clergymen during the English civil wars and Interregnum. The politics of martyrdom to be derived from letters to John Walker was grounded on the correspondents' conviction that their epistles conveyed accounts of sequestered clergymen and their families who had suffered for their profession of Christian truth. The persecutions that loyal clergy had endured during the 1640s and 1650s were signs that the Church by law established, both then and now, was the true English Church. Furthermore, as documentary witnesses to oral testimonies which identified the genuine sufferers for Christian truth within recent memory, the epistles themselves aspired to be martyrological relics.